A rare case of lung cancer presenting as an ischioanal fossa mass - Shetty, Nishitha; Singh, Ranvijay; Naveed, Maryam; Ronghe, Ashwini M; Barot, Falguni Shashikant (Indian Journal of Medical and Paediatric Oncology, 2016)
Lung cancer metastasis commonly involves the adrenal glands, liver, bone, and brain. However, it can have some rarer forms of metastatic presentation making diagnosis difficult, especially in nonsmokers. We describe a rare case of lung cancer with metastasis to the ischioanal fossa. Overall, this case emphasizes that consideration should be given to wide range of diagnosis in atypical cases of anorectal masses. Lung cancer presenting as an ischioanal mass is not reported so far.
Keywords: Ischioanal fossa; lung cancer; metastasis